2021
DOI: 10.3389/frobt.2021.650906
|View full text |Cite
|
Sign up to set email alerts
|

Technical Challenges for Smooth Interaction With Seniors With Dementia: Lessons From Humanitude™

Abstract: Due to cognitive and socio-emotional decline and mental diseases, senior citizens, especially people with dementia (PwD), struggle to interact smoothly with their caregivers. Therefore, various care techniques have been proposed to develop good relationships with seniors. Among them, Humanitude is one promising technique that provides caregivers with useful interaction skills to improve their relationships with PwD, from four perspectives: face-to-face interaction, verbal communication, touch interaction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…However, it remains unknown whether agents other than humans, specifically robots, could provide pleasant touch that functions similar to humans’ touch. Robots capable of providing such a pleasant touch could help alleviate problems by a lack of caregivers and thereby improve the quality of caregiving generally [ 12 , 13 ]. Some previous studies have shown that touch by a robot can provide a positive effect for humans [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unknown whether agents other than humans, specifically robots, could provide pleasant touch that functions similar to humans’ touch. Robots capable of providing such a pleasant touch could help alleviate problems by a lack of caregivers and thereby improve the quality of caregiving generally [ 12 , 13 ]. Some previous studies have shown that touch by a robot can provide a positive effect for humans [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was observed that the elderly engaged more with the robot from one session to the next, showing a positive perception of interaction with it. In several studies, it has been argued that humanoid robots are a suitable tool for use with dementia patients, as well as with relatives and caregivers and that their presence brings patients with dementia in a more positive emotional state [ 27 , 28 ]. In particular, music sessions stimulate patients to recall memories and talk about their past [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our video analysis via AI was developed to analyse healthcare professionals’ multimodal communication, that is, their face-to-face interaction, verbal communication and touch interaction. 19 25 Our system collects the viewpoints of participants using a wearable eye-tracking system during a simulated patient encounter, performs facial landmark detection and deep learning-based analyses to detect eye contact, obtains the total utterances from the data of fixed videos and detect the touch duration by annotation of the fixed videos. This study thus quantitatively analyses the communication skills of physicians for geriatric care following their multimodal comprehensive care communication skills training.…”
Section: Introductionmentioning
confidence: 99%